2013
DOI: 10.1155/2013/952321
|View full text |Cite
|
Sign up to set email alerts
|

Future of Management of Multiple Sclerosis in the Middle East: A Consensus View from Specialists in Ten Countries

Abstract: The prevalence of multiple sclerosis (MS) is now considered to be medium-to-high in the Middle East and is rising, particularly among women. While the characteristics of the disease and the response of patients to disease-modifying therapies are generally comparable between the Middle East and other areas, significant barriers to achieving optimal care for MS exist in these developing nations. A group of physicians involved in the management of MS in ten Middle Eastern countries met to consider the future of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…A similar increase has also been recorded in regions previously considered at low-risk for MS, like Middle-East [18][19][20] and South and East Asia [21]. This worldwide trend seems not to be related to the increased survival of MS patients due to more effective treatments, better management of symptoms and comorbidities, and/or to an earlier diagnosis of MS. As a matter of fact, the slopes of MS incidence and prevalence have significantly changed in the second part of the 20th century strongly pointing out the role of exogenous/environmental agents in determining the risk of MS. Interestingly, the mortality rate did not significantly change over the last 3 decades.…”
Section: Discussionsupporting
confidence: 71%
“…A similar increase has also been recorded in regions previously considered at low-risk for MS, like Middle-East [18][19][20] and South and East Asia [21]. This worldwide trend seems not to be related to the increased survival of MS patients due to more effective treatments, better management of symptoms and comorbidities, and/or to an earlier diagnosis of MS. As a matter of fact, the slopes of MS incidence and prevalence have significantly changed in the second part of the 20th century strongly pointing out the role of exogenous/environmental agents in determining the risk of MS. Interestingly, the mortality rate did not significantly change over the last 3 decades.…”
Section: Discussionsupporting
confidence: 71%
“…Employers do not understand that patients with MS may require more sick leaves than others or need more time to accomplish certain tasks. In this regard, and as the number of MS patients is increasing in Jordan (Aljumah et al, ), we believe that there is a need for support systems and services that enable people with MS to continue employment as long as they are productive and have desire to work. Income security programs that are comprehensive and flexible enough to allow persons with episodic, recurring illnesses to work whenever possible without losing access to income support when ill and unemployed are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Employers do not understand that patients with MS may require more sick leaves than others or need more time to accomplish certain tasks. In this regard, and as the number of MS patients is increasing in Jordan (Aljumah et al, 2013) (Bergen, 2002;World Health Organization, 2004). Furthermore, based on a survey by WHO, the number of nurses for MS in the world ranged from 0 to 0.07 per 100,000.…”
Section: Lack Of Awareness About Ms Rehabilitationmentioning
confidence: 99%
“…The recently reported increased prevalence of MS in the Middle East (6), the Gulf region (7,8) and in Bahrain (Alsharoqi et al, 2014, unpublished data, where prevalence was found to be 50/100,1000) has stimulated the study of differential gene expression in Bahraini MS patients with an insight to detect novel genes that may correlate with the pathogenesis of MS.…”
Section: Discussionmentioning
confidence: 99%
“…There is a universal increase in the prevalence and incidence of MS over time. In the Middle East, and particularly the Gulf region, an increased prevalence has been recently reported (6)(7)(8) due to genetic and environmental factors, particularly following the most recent wars in the region (9), with a similar increase in Bahrain (Alsharoqi et al, 2014, unpublished data).…”
Section: Introductionmentioning
confidence: 97%